Assembly of Multiple Full‐Size Genes or Genomic DNA Fragments on Human Artificial Chromosomes Using the Iterative Integration System. Issue 12 (17th December 2021) - Lee, Nicholas C. O.; Petrov, Nikolai S.; Larionov, Vladimir; Kouprina, Natalay
Abstract: Human artificial chromosomes (HACs) are gene delivery vectors that have been used for decades for gene functional studies. HACs have several advantages over viral‐based gene transfer systems, including stable episomal maintenance in a single copy in the cell and the ability to carry up to megabase‐sized genomic DNA segments. We have previously developed the alphoid tetO ‐HAC, which has a single gene acceptor loxP site that allows insertion of an individual gene of interest using Chinese hamster ovary (CHO) hybrid cells. The HAC, along with a DNA segment of interest, can then be transferred from donor CHO cells to various recipient cells of interest via microcell‐mediated chromosome transfer (MMCT). Here, we detail a protocol for loading multiple genomic DNA segments or genes into the alphoid tetO ‐HAC vector using an iterative integration system (IIS) that utilizes recombinases Cre, ΦC31, and ΦBT. This IIS‐alphoid tetO ‐HAC can be used for either serially assembling genomic loci or fragments of a large gene, or for inserting multiple genes into the same artificial chromosome. The insertions are executed iteratively, whereby each round results in the insertion of a new DNA segment of interest. This is accompanied by changes of expression of marker fluorescent proteins, which simplifies screening of correct clones, and changes of selection and counterselection markers, which constitutes an error‐proofing mechanism that removes mis‐incorporated DNA segments. In addition, the IIS‐alphoid tetO ‐HAC carrying the genes can be eliminated from the cells, offering the possibility to compare the phenotypes of human cells with and without functional copies of the genes of interest. The resulting HAC molecules may be used to investigate biomedically relevant pathways or the regulation of multiple genes, and to potentially engineer synthetic chromosomes with a specific set of genes of interest. The IIS‐alphoid tetO ‐HAC system is expected to be beneficial in creating multiple‐gene humanized models with the purpose of understanding complex multi‐gene genetic disorders. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Integration of the first DNA segment of interest into the IIS‐alphoid teto ‐HAC Basic Protocol 2 : Integration of a second DNA segment of interest into the IIS‐alphoid teto ‐HAC Basic Protocol 3 : Integration of a third DNA segment of interest into the IIS‐alphoid teto ‐HAC Support Protocol : Fluorescence in situ hybridization analysis for the circular IIS‐alphoid tetO ‐HAC